2007
DOI: 10.1517/13543784.16.11.1775
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against nicotine: an emerging therapy for tobacco dependence

Abstract: Tobacco dependence is an addiction characterised by compulsive drug-seeking and drug-taking behavior and intensive craving in the absence of tobacco. Nicotine is the major addictive component of tobacco and acts on the reward system in the brain. Together with strong conditional reinforcements, unaided smoking cessation attempts are notoriously unsuccessful and even the most recently introduced pharmacotherapy, varenicline, only achieves a 23% continuous abstinence rate after 1 year. Vaccination against nicoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 47 publications
0
51
0
Order By: Relevance
“…Using this approach to vaccine design, we have previously demonstrated that levels of neutralizing Ab responses against self-proteins can be induced that are high enough to show therapeutic effectiveness in mice (31)(32)(33)(34)(35). We have also demonstrated that efficacy established in animal models can be translated into efficacy in humans (47,48). An important safety feature and advantage of VLP-based vaccines is that autoantibodies can be induced without the addition of powerful adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach to vaccine design, we have previously demonstrated that levels of neutralizing Ab responses against self-proteins can be induced that are high enough to show therapeutic effectiveness in mice (31)(32)(33)(34)(35). We have also demonstrated that efficacy established in animal models can be translated into efficacy in humans (47,48). An important safety feature and advantage of VLP-based vaccines is that autoantibodies can be induced without the addition of powerful adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…Some progress is being made in developing vaccines which modulate the course of diabetes and hypertension [42]. Vaccination against addiction, including smoking, is also feasible, although very high antibody concentrations are required to achieve an effect [43], and there are early results suggesting that vaccination against Alzheimer's disease might slow the progress of this condition [44]. In the coming decades, vaccination is likely to expand its scope beyond prevention of the common infections of childhood which has been its main success so far.…”
Section: The Long-term Future Of Vaccinationmentioning
confidence: 99%
“…Upon inhalation of cigarette smoke, nicotine passes into the bloodstream and, within seconds, crosses the bloodbrain barrier to enter the brain, where it causes the release of dopamine and exerts its addictive effects. Nicotine addiction vaccines work by causing the immune system to produce nicotine antibodies, which bind to nicotine and prevent it from crossing the bloodbrain barrier [Maurer and Bachmann, 2007]. This removes the pleasurable stimulus in the brain that is normally caused by nicotine.…”
Section: Nicotine Vaccinesmentioning
confidence: 99%